The Unsung Saga of ECCE in RTE 2009 - Chowdhury, Rita (JOURNAL OF INDIAN EDUCATION, 2018)
Education is neither a need nor a privilege but a necessity for the exercise of all other human rights. It brings about a blossoming of mental faculties and transforms a raw, unlettered human being into an accountable member of the society. Children are the essence of any educational system and reforms. A child’s mind grows at an extraordinary pace during the initial six years of one’s life and lays the foundation for lifelong development. This important aspect of education has faced negligence by the Right to Free and Compulsory Education Act, 2009, which was otherwise a revolutionary step taken by the Government of India (GoI). The present article aims at reflecting the necessity to review Section 11 of Right to Free and Compulsory Education Act, 2009 and bring necessary amendments for the successful realisation of universalisation of elementary education.